Integrating eco-sufism into the hidden curriculum of islamic boarding schools to develop environmentally aware religious character among students - Andri Sutrisno; Dwi Ari Kurniawati; M. Mas’ud Said (12 Waiheru, 2026)
This study is motivated by the environmental crisis, which calls for a holistic approach grounded in religious values, particularly within the Islamic Boarding School environment. However, there has been little research that thoroughly examines how Islamic Boarding Schools integrate the values of Eco-sufism through the hidden curriculum to foster religious character that is environmentally conscious. This study aims to: (1) describe a model for integrating Eco-sufism through the hidden curriculum to foster students’ religious character; (2) identify the Eco-sufism values instilled through the hidden curriculum to enhance character education that is environmentally conscious; and (3) analyze the implications of Eco-sufism integration on students’ ecological behavior at Al-Amien Prenduan Islamic Boarding School. The approach used is a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The informants were the leaders and caregivers, teachers, and students. The research was conducted from April 2025 to December 2025. Data analysis involved data reduction, data presentation, and drawing conclusions. The results of the study indicate that the model of Eco-sufism integration is manifested in the exemplary conduct of the kiai, daily routines, and the boarding school’s spatial layout, all of which are rich in ecological meaning. The internalized values include simplicity, balance with nature, and responsibility as stewards of the earth. Consequently, there is a shift in the students’ ecological behavior, characterized by an awareness of maintaining cleanliness, managing resources, and caring for environmental sustainability. This study confirms that an Eco-sufism-based hidden curriculum effectively shapes the students’ religious and ecological character in an integrated manner.